Coffee Consumption Factor on Increasing of Alertness and Decreassing of the Risk of Accidents; Analysis Using Bayessian Network - Lumba, Pada; Rismalinda; Fathoni, Ahmad (Aptek, 2025)
Most of the motorcyclists feel exhausted before they had accident. 50.5% of motorcyclists who have accident sleep at night before the accident for 6 hours and below. The sample consist of 381 respondents who had experienced accident. Data analysis used GeNie 2.0 software. The results show that the motorcyclists who consume coffee are more likely to have accident by 11% and 89% for the motorcyclists who do not consume coffee . The results of the model validation show the Mean Absolute Deviation (MAD) value was 21.07%. Scenario 1 shows that motorcyclists who consume coffee and sleep less than normal sleeping hours have the potential to have accidents. The drivers who drink coffee and drive on a straight road are more likely to have accident than driving on hills or bends. In scenario 3, the road geometry has no effect on the level of fatigue and the probability of accidents that occurred for drivers who consume coffee. In scenario 4 shows that the longer the driving time, thus the driver's fatigue level increases. However, the driver's fatigue level decreases when long duration of driving is over 60 minutes and it is caused by the driver has rested due to the driver is fatigue. Scenario 5 shows that drivers who consume coffee and have side job are more likely to experience fatigue and tend to have accident than drivers who do not consume coffee and the drivers do not have side job.